ปัจจัยที่มีผลต่อเจตคติและความสามารถในการแก้ปัญหาทางคณิตศาสตร์ ของนักเรียนชั้นมัธยมศึกษาปีที่ 1 โรงเรียนสาธิตมหาวิทยาลัยรามคำแหง - หาญห้าว, สำรวย (วารสารวิชาการศึกษาศาสตร์ ศรีนครินทรวิโรฒ, 2017)
บทคัดย่อ การวิจัยครั้งนี้มีวัตถุประสงค์ เพื่อศึกษาความสัมพันธ์ระหว่างปัจจัย เพศ จำนวนชั่วโมงที่เรียนเสริม (เรียนพิเศษ) จำนวนที่ค้นคว้าด้วยตนเอง ด้านพฤติกรรมการสอนของครูตามการรับรู้ของนักเรียน ด้านแรงจูงใจใฝ่สัมฤทธิ์ทางการเรียน ด้านการรับรู้ความสามารถของตนเองในการเรียนคณิตศาสตร์ กับเจตคติและความสามารถในการแก้ปัญหาทางคณิตศาสตร์ และเพื่อศึกษาค่าน้ำหนักความสำคัญของปัจจัยด้านจำนวนชั่วโมงที่เรียนเสริม (เรียนพิเศษ) จำนวนชั่วโมงศึกษาค้นคว้าด้วยตนเอง ด้านพฤติกรรมการสอนของครูตามการรับรู้ของนักเรียน ด้านแรงจูงใจใฝ่สัมฤทธิ์ทางการเรียนและด้านการรับรู้ความสามารถของตนเองในการเรียนคณิตศาสตร์ ที่มีผลต่อเจตคติและความสามารถในการแก้ปัญหาทางคณิตศาสตร์กลุ่มตัวอย่างเป็นนักเรียนชั้นมัธยมศึกษาปีที่ 1 โรงเรียนสาธิตมหาวิทยาลัยรามคำแหง จำนวน 250 คน เครื่องมือที่ใช้ในการวิจัยผู้วิจัยใช้จำนวน 2 ฉบับ ฉบับที่ 1 แบบทดสอบวัดความสามารถในการแก้ปัญหาทางคณิตศาสตร์ ฉบับที่ 2 แบบสอบถาม การวิเคราะห์ข้อมูล ได้แก่ ค่าสัมประสิทธิ์สหสัมพันธ์พอยท์ไบซีเรีย ค่าสัมประสิทธิ์สหสัมพันธ์เพียร์สัน และหาค่าสัมประสิทธิ์สหพันธ์พหุคูณ ทำการทดสอบนัยสำคัญทางสถิติ F-test และหาค่าสัมประสิทธิ์ของตัวแปรที่มีผลต่อเจตคติและความสามารถในการแก้ปัญหาทางคณิตศาสตร์ โดยใช้การถดถอยพหุคูณทำการทดสอบความมีนัยสำคัญทางสถิติค่า t – test ผลการวิจัยสรุปได้ดังนี้ 1. ค่าน้ำหนักความสำคัญของปัจจัยการรับรู้ความสามารถของตนเองในการเรียนคณิตศาสตร์ (x6) และพฤติกรรมการสอนของครูตามการรับรู้ของนักเรียน (x4) ส่งผลต่อเจตคติต่อวิชาคณิตศาสตร์ (y1) ในทางบวกอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 โดยมีค่าน้ำหนักความสำคัญในรูปคะแนนมาตรฐาน เท่ากับ .650 และ .190 และค่าน้ำหนักความสำคัญของปัจจัยพฤติกรรมการสอนของครูตามการรับรู้ของนักเรียน (x4) ส่งผลต่อความสามารถในการแก้ปัญหาทางคณิตศาสตร์ (y2) ในทางบวกอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 โดยมีค่าน้ำหนักความสำคัญในรูปคะแนนมาตรฐานเท่ากับ .4541. ค่าสัมประสิทธิ์สหสัมพันธ์ ด้านเพศ (x1) กับเจตคติต่อวิชาคณิตศาสตร์ (y1) มีความสัมพันธ์ทางลบกับเจตคติต่อ วิชาคณิตศาสตร์ (y1) อย่างมีนัยสำคัญทางสถิติที่ระดับ.05และมีความสัมพันธ์ทางลบกับความสามารถในการแก้ปัญหาทาง คณิตศาสตร์ ( Y2) อย่างไม่มีนัยสำคัญทางสถิติมีค่าเท่ากับ -.270 และ -.40 ค่าสัมประสิทธิ์สหสัมพันธ์ ด้านจำนวนชั่วโมงที่เรียนเสริม (เรียนพิเศษ) ( ) มีความสัมพันธ์ทางลบกับเจตคติต่อวิชาคณิตศาสตร์ ( ) และความสามารถในการแก้ปัญหาทางคณิตศาสตร์ ( ) อย่างไม่มีนัยสำคัญทางสถิติ มีค่าเท่ากับ -.23 และ -.39 ค่าสัมประสิทธิ์สหสัมพันธ์ จำนวนชั่วโมงที่ค้นคว้าด้วยตนเอง ( ) มีความสัมพันธ์ทางลบกับเจตคติต่อวิชาคณิตศาสตร์ ( ) และความสามารถในการแก้ปัญหาทางคณิตศาสตร์ ( ) อย่างไม่มีนัยสำคัญทางสถิติมีค่าเท่ากับ -.24 และ -.23 ค่าสัมประสิทธิ์สหสัมพันธ์ด้านพฤติกรรมการสอนของครูตามการรับรู้ของนักเรียน (x4), ด้านแรงจูงใจใฝ่สัมฤทธิ์ทางการเรียน (x5) และด้านการรับรู้ความสามารถของตนเองในการเรียนคณิตศาสตร์ (x6) มีความสัมพันธ์ทางบวกกับเจตคติต่อวิชาคณิตศาสตร์( )และความสามารถในการแก้ปัญหาทางคณิตศาสตร์ ( ) อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 มีค่าเท่ากับ (.428, .373), (.336, .135) และ (.638, .269) ตามลำดับ 3. ค่าสัมประสิทธิ์สหสัมพันธ์พหูคูณระหว่างปัจจัยทั้ง 6 ตัวแปรกับเจตคติต่อวิชาคณิตศาสตร์ (Y1) และความสามารถในการแก้ปัญหาทางคณิตศาสตร์ (Y2) มีค่าเท่ากับ .815 และ .483 ซึ่งมีสัมพันธ์กันอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 โดยปัจจัยทั้งหมดร่วมกันอธิบายความแปรปรวนของเจตคติต่อวิชาคณิตศาสตร์ ( ) และความสามารถในการแก้ปัญหาทางคณิตศาสตร์ (Y2) ได้ร้อยละ 66.40 และ 23.30 ตามลำดับ คำสำคัญ : เจตคติ, ความสามารถในการแก้ปัญหาทางคณิตศาสตร์ ABSTRACT In this research investigation, the researcher examines (1) the relationships between the factors of gender, the number of hours of supplementary study (special tuition); the number of hours of self-study; the aspect of the teaching behaviors of teachers the aspect of academic achievement motivation; the aspect of self-efficacy in the study of mathematics, and attitudes vis-à-vis the mathematical problem-solving ability (2) the statistical significance of the weights of the factors mentioned by virtue of which effects are exerted on the attitudes and the mathematical problem-solving ability of the students under study. The researcher selected the members of the sample population of 250 Matthayom Sueksa One students .The research instruments consisted of a test used for testing mathematical problem-solving ability and a quintipartite questionnaire. The techniques of descriptive statistics consisted of the correlation coefficients between variables were determined using the point biserial correlation coefficient (rpb) and Pearson’s product moment correlation coefficient (PPMCC) methods. Moreover, multiple regression analysis was applied, thereby allowing the computation of multiple correlations (R) between variables. Statistical significance was established using the F-test technique. The coefficients of variables exerting effects on mathematical problem solving were determined using multiple regression analysis. In this last case, statistical significance was determined using a t test technique. Findings are as follows: 1. The factorial variable of gender (X1) was negatively correlated with attitudes toward mathematics (Y1), at the statistically significant level of .05 in addition to being negatively correlated with mathematical problem-solving ability (Y2), but not at a statistically significant level were -.270 and -.40 respectively. The correlation coefficients between the variables of the number of hours of supplementary study (special tuition) (X2) was negatively correlated with attitudes toward mathematics (Y1)and mathematical problem-solving ability (Y2) ), but not at a statistically significant level were -.23 and -.39 respectively. The correlation coefficients between the variables of the number of hours of self-study (X3) was negatively correlated with attitudes toward mathematics (Y1)and mathematical problem-solving ability (Y2) ), but not at a statistically significant level were -.24 and -.23 respectively. The correlation coefficients between the variables of the teaching behaviors of teachers by reference to student perception (X4); academic achievement motivation (X5); and self-efficacy in the study of mathematics (X6) showed that these variables were positively correlated with attitudes toward mathematics (Y1) and mathematical problem-solving ability (Y2) at the statistically significant level of .05. Were (.428 , .373 ), ( .336 , .135) and ( .638 , .269 ) respectively. 2. It was also found that the weight of significance of the variables of self-efficacy in the study of mathematics (X6) and the teaching behaviors of teachers by reference to student perception (X4) exerted positive effects on attitudes toward mathematics (Y1) at the statistically significant level of .05. Furthermore, the weights of significance in the form of standard scores beta (β) were 0.650 and 0.190, respectively. It was additionally found, finally, that the teaching behaviors of teachers by reference to student perception (X4) exerted positive effects on mathematical problem-solving ability (Y2) at the statistically significant level of .05, while the weight of significance in the form of standard score beta (β) was at 0.454. 3. The multiple correlation coefficient between gender (X1) ,number of hours of supplementary study (special tuition) (X2) ,number of hours of self-study (X3) ,the teaching behaviors of teachers by reference to student perception (X4), academic achievement motivation (X5) , self-efficacy in the study of mathematics (X6), attitudes toward mathematics (Y1) and mathematical problem-solving ability (Y2) were .815 and .483. which were statistically significant at .05. All factors explained variance of attitudes toward mathematics (Y1)and mathematical problem-solving ability (Y2) at 66.40 and 23.30 percentage respectively. Keywords : Attitudes, Mathematical Problem Solving Ability